Social network analysis of intergovernmental relations and policy tools in China’s coastal reclamation management - Gong, Hongbo; He, Xiangmei; Li, Jialin; Tian, Peng; Ai, Shunyi; Liu, Yongchao (Frontiers in Marine Science, 2024)
As an effective means of sea development and utilization, high-intensity coastal reclamation activities lead to increasingly prominent ecological problems, necessitating strict control measures. The accurate implementation of policies is paramount in managing and controlling coastal reclamation. However, current quantitative research on the policy texts related to coastal reclamation management and control is lacking. The specific control measures within these policies remain unclear, and there is a dearth of attention to the implicit intergovernmental relationships they entail. To address this gap, we reviewed China's coastal reclamation management and control policies from 1978 to 2022. Utilizing content analysis and social network analysis, we constructed a policy network to explore the evolution of intergovernmental relations and the habitual combination of policy tools in coastal reclamation management and control. Our findings reveal (1) The intergovernmental relations of reclamation management and control agencies have evolved from simple to complex, with key departments becoming increasingly prominent; (2) Environmental considerations form the mainstay of policy tools for reclamation control, highlighting an imbalance between supply-side and demand-side approaches; (3) Since 1999, the interactive network between intergovernmental relations and policy tools has begun to exhibit a distinct core-periphery structure, and the social circle has gradually expanded to form a social circle consisting of 23 administrative departments and most departmental policy tools, while there are also some independent working factions at different stages; (4) Policy sustainability is currently inadequate, and in the later stages of management and control, there is a noticeable conflict within the policy texts. The application of social network analysis methods visualizes the policy tools used in coastal reclamation and their underlying intergovernmental relations. This approach is instrumental in accurately monitoring the progress of coastal reclamation management and control, providing a decision-making reference for subsequent policies in this area.